PROGRAM PENGEMBANGAN USAHA MINA PEDESAAN (PUMP) BIDANG PENGOLAHAN DAN PEMASARAN HASIL PERIKANAN (P2HP) DAN PENDAPATAN PELAKU USAHA BIDANG PERIKANAN DI WILAYAH PESISIR KOTA BANDAR LAMPUNG - Sinta Dias Dewantary; Tubagus Hasanuddin; Begem Viantimala (Lampung University, 2015)
The purposes of this research are to analyze the performance of PUMP program in Bandar Lampung, the revenue of fisheries businessmen before and after implementing PUMP program in Bandar Lampung, and the constraint of PUMP program in Bandar Lampung. This research was conducted in Bumi Waras Sub-district of Bandar Lampung. This research applied census method by involving 77 fisheries businessmen as the subject of PUMP program. The research data was analyzed by descriptive and statistics comparative test. The results of this research showed that the performance of PUMP program in Bandar Lampung was good. The income of fisheries businessmen before taking the program was Rp5,094,759.70 and the income of fisheries businessmen after taking the program became Rp5,067,661.89. a There were some problems during the implementation of the PUMP program in Bandar Lampung, such as some of the program’s target was less appropriate, less assistants, and the program’s target was lack of guidance. Key words: fisheries, performance, PUMP, revenue